Complex mixtures : methods for in vivo toxicity testing (National Academy Press, 1988)
Addresses the problem of identifying and classifying complex mixtures, investigating the effect of exposure, and the research problems inherent in testing their toxicity to human beings. A series of case studies is presented, including one that examines the cofactors of alcohol consumption and cigarette smoke.